2001
DOI: 10.1016/s0896-6273(01)00188-x
|View full text |Cite
|
Sign up to set email alerts
|

Released GFRα1 Potentiates Downstream Signaling, Neuronal Survival, and Differentiation via a Novel Mechanism of Recruitment of c-Ret to Lipid Rafts

Abstract: Although both c-Ret and GFRalpha1 are required for responsiveness to GDNF, GFRalpha1 is widely expressed in the absence of c-Ret, suggesting alternative roles for "ectopic" sites of GFRalpha1 expression. We show that GFRalpha1 is released by neuronal cells, Schwann cells, and injured sciatic nerve. c-Ret stimulation in trans by soluble or immobilized GFRalpha1 potentiates downstream signaling, neurite outgrowth, and neuronal survival, and elicits dramatic localized expansions of axons and growth cones. Soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
261
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(277 citation statements)
references
References 36 publications
14
261
0
2
Order By: Relevance
“…Because the effect is seen in DBA͞2J heterozygotes, it likely results from a dominant allele(s). In some neural cells, c-Ret stimulation by soluble GFR␣1 potentiates and modulates downstream signaling (19), which may account for the essential nature of soluble GFR␣1 for proliferation of SSCs in most mouse strains. bFGF is a crucial factor for in vitro proliferation of PGCs (20,21), and the requirement for this factor apparently continues when SSCs form germ cell clumps in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the effect is seen in DBA͞2J heterozygotes, it likely results from a dominant allele(s). In some neural cells, c-Ret stimulation by soluble GFR␣1 potentiates and modulates downstream signaling (19), which may account for the essential nature of soluble GFR␣1 for proliferation of SSCs in most mouse strains. bFGF is a crucial factor for in vitro proliferation of PGCs (20,21), and the requirement for this factor apparently continues when SSCs form germ cell clumps in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular responses to GDNF are mediated by a multicomponent receptor complex consisting of c-Ret receptor tyrosine kinase and a glycosyl phosphatidylinositol-anchored ligand-binding subunit, GFR␣1, in many cell types (9). Although it has been shown that mouse spermatogonia express GFR␣1 (10, 11), we reasoned that adding soluble GFR␣1 molecules might potentiate the stimulatory signal through the c-Ret receptor or modulate the signaling pathways (19). In addition, bFGF, a critical growth factor for primordial germ cells (PGCs) in vitro (20,21), was examined.…”
Section: Sscs Derived From Dba͞2j-background Mice Can Be Cultured Inmentioning
confidence: 98%
“…It has been proposed that these lipid microdomains function through their capacity to promote certain protein-protein interactions but prevent others, leading to the establishment of a different signaling environment in rafts versus nonrafts (Simons and Toomre, 2001). This kind of regulation appears to be a common phenomenon because other receptor tyrosine kinases such as c-Ret also have been shown to have different signaling properties dependent on their location inside versus outside of raft-like structures (Tansey et al, 2000;Paratcha et al, 2001). This concept implies that mechanisms/molecules that shift TrkB into raft-like structures or promote longer TrkB residence in this environment will have an impact on the signaling of TrkB.…”
Section: The Cc2 Domain Of Trkb Mediates the Interaction With Ephrinasmentioning
confidence: 99%
“…Although information on signal transduction downstream of the MEN2A mutated RET (MEN2A-RET) receptor is still limited, it has been demonstrated that several tyrosine residues are autophosphorylated in MEN2A-RET, including tyr905, tyr1015, tyr1062 and tyr1096 which serve as docking sites for Grb7/Grb10/ Grb14, phospholipase Cg, Shc/Enigma or FRS2, and Grb2, respectively (Borrello et al, 1996;Paratcha et al, 2001;Kurokawa et al, 2001;Durick et al, 1996;Liu et al, 1996;Pandey et al, 1996;Arighi et al, 1997;Lorenzo et al, 1997;Alberti et al, 1998). Consequently, the Ras/ERK, JNK and PI-3K signal transduction pathways are activated by MEN2A-RET.…”
Section: Introductionmentioning
confidence: 99%